Expression of receptor activator of nuclear factor kappa‐B as a poor prognostic marker in breast cancer. Issue 7 (11th August 2014) - Park, Hyung Seok; Lee, Ahwon; Chae, Byung Joo; Bae, Ja‐Seong; Song, Byung Joo; Jung, Sang Seol
Abstract Purpose Receptor activator of nuclear factor kappa‐B and its ligand (RANK/RANKL) and Osteoprotegerin (OPG) are key molecules for regulating osteoclastic activity in bone. However, little is known about the role of RANK‐related molecules in breast cancer prognosis. We aimed to evaluate RANK, RANKL, and OPG expression and the associated clinical impact in breast cancer. Methods Tissue microarray (TMA) from 185 patients with primary breast cancer was established. Immunohistochemistry for RANK, RANKL, and OPG was performed. Clinicopathologic features and survival outcomes associated with expression of RANK, RANKL, and OPG were analyzed. Results RANK, RANKL, and OPG were expressed in 74.1%, 78.4%, and 45.9% of patients, respectively. RANKL expression was associated with lower Ki‐67 level. OPG expression was related to small tumor size, node negativity, and low Ki‐67. There was no significant difference in clinicopathologic features between tumors with RANK and those without RANK. RANK expression was significantly associated with poor disease‐free survival in univariate analysis (P = 0.04) and multivariate analysis (P = 0.02). RANKL expression was associated with improved skeletal disease‐free survival in multivariate analysis (P = 0.03). Conclusions The RANK/RANKL pathway regulated by OPG may have a role in predicting progression and prognosis of breast cancer. J. Surg. Oncol. 2014 110:807–812. © 2014 Wiley Periodicals, Inc.